2022
DOI: 10.1155/2022/2099268
|View full text |Cite|
|
Sign up to set email alerts
|

Karst Collapse Monitoring and Early Warning Evaluation Method Based on Multisensor Internet of Things

Abstract: The international community has paid extensive attention to the numerous engineering problems faced by karst areas caused by the increasingly frequent human activities. China has a wide variety of karst forms. Among them, carbonate karst is the most widely distributed, and the development of carbonate karst is relatively strong in many areas. Countless property losses are caused by karst disasters every year. This article aims to study the real-time monitoring and timely early warning of karst collapse through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The development of a karst collapse is closely correlated with the air–water pressure in the underground karst channel. , To monitor the karst collapse hazard caused by groundwater activities in rock formations, groundwater level and water–air pressure sensors are placed in karst cavities in karst areas to monitor groundwater level data and water–air pressure. Pan et al monitored the groundwater variation process in a closed mine in a karst area, and they found many sinkhole collapses were caused by the groundwater level fluctuation . In terms of air pressure monitoring, many techniques were developed including an automatic monitoring method of the water–air pressure sensor, dynamic real-time groundwater monitoring, and Internet of Things technology, which have been used in field monitoring and for early warning of karst collapse. , Jiang, Lei, and Zhao developed the specific air pressure monitoring techniques for karst collapse monitoring and used them to monitor many field karst collapses. , They collected a large amount of air pressure data caused by groundwater level fluctuation, which is useful in karst collapse predication. Overall, the groundwater activity can lead to high air–water pressure and induce karst collapse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of a karst collapse is closely correlated with the air–water pressure in the underground karst channel. , To monitor the karst collapse hazard caused by groundwater activities in rock formations, groundwater level and water–air pressure sensors are placed in karst cavities in karst areas to monitor groundwater level data and water–air pressure. Pan et al monitored the groundwater variation process in a closed mine in a karst area, and they found many sinkhole collapses were caused by the groundwater level fluctuation . In terms of air pressure monitoring, many techniques were developed including an automatic monitoring method of the water–air pressure sensor, dynamic real-time groundwater monitoring, and Internet of Things technology, which have been used in field monitoring and for early warning of karst collapse. , Jiang, Lei, and Zhao developed the specific air pressure monitoring techniques for karst collapse monitoring and used them to monitor many field karst collapses. , They collected a large amount of air pressure data caused by groundwater level fluctuation, which is useful in karst collapse predication. Overall, the groundwater activity can lead to high air–water pressure and induce karst collapse.…”
Section: Introductionmentioning
confidence: 99%
“… 6 8 Pan et al monitored the groundwater variation process in a closed mine in a karst area, and they found many sinkhole collapses were caused by the groundwater level fluctuation. 9 In terms of air pressure monitoring, many techniques were developed including an automatic monitoring method of the water–air pressure sensor, 10 − 12 dynamic real-time groundwater monitoring, 13 − 16 and Internet of Things technology, 17 19 which have been used in field monitoring and for early warning of karst collapse. 20 , 21 Jiang, Lei, and Zhao developed the specific air pressure monitoring techniques for karst collapse monitoring 22 and used them to monitor many field karst collapses.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%